Phenological Growth Stages of The Golden Penda Tree (Xanthostemon chrysanthus) - Nazarudin, M.R.A.; Adzmi, Y.; Normaniza, O.; Tsan, F.Y. (2012)
Biologishe Bundesanstalt, Bundessortenamt and CHemical Industry (BBCH) scales are a system for the uniform coding of phenologically similar growth stages of plants, using a two-digit decimal code. This paper describes the phenological growth stages of a landscape tree, Xanthostemon chrysanthus using the BBCH-scale. Detailed descriptions of principal growth stages for bud, leaf and shoot development, inflorescence emergence, flowering, fruit development, maturity or ripening of fruit and seed, and other secondary growth stages are provided. The developed scale will be of great help to landscape managers and researchers for better communication, more efficient planning of management practices and experiments of flowering trees.